Philorhizus occitanus sp. n. from the South-Western Alps (Piedmont, Italy) (Coleoptera: Carabidae, Dromiini) - Allegro, Gianni; Giachino, Pier Mauro; Bisio, Luigi; Giuntelli, Piero (Fragmenta entomologica, 2015)
Philorhizus occitanus sp. n. from the South-Western Alps (Ellero Valley and Maira Valley) is described. This new species is similar to P. crucifer and P. notatus as far as the external morphology is concerned, but it is distinguished by the color pattern and the shape of elytra, as well as by the features of the median lobe of aedeagus. P. liguricus, which is easily distinguished from P. occitanus sp. n. by the external morphology, was already recorded from the South-Western Alps and from the Ligurian Apennines. P. occitanus sp. n. is a likely close relative of P. notatus, although the affinities of this relict flightless new species remain uncertain.